Large-scale thermochemistry calculations for combustion models - Kiran K. Yalamanchi; Yang Li; Tairan Wang; M. Monge-Palacios; S. Mani Sarathy (Applications in Energy and Combustion Science, 2022)
Accurate thermochemical properties for chemical species are of vital importance in combustion chemistry research. Group additivity approaches are widely used to generate thermochemistry data used in chemical kinetic models, but this approach has limited accuracy. Following on previous studies by the combustion community, we performed electronic structure calculations to obtain reliable thermochemistry data for a large set of molecules taken from a well-established chemical kinetic model. The developed database consists of 1340 species that contain up to 18 and 5 carbon and oxygen atoms, respectively. The M06-2X/aug-cc-pVTZ level of theory was used for the geometry optimizations, vibrational frequency calculations, and dihedral angle scans. The potential energy of the different species was further refined with different composite methods, and the G3 method with the atomization reaction approach was selected to calculate the enthalpy of formation at 0 K. This information was then used in statistical thermodynamics calculations to obtain standard enthalpies of formation and entropy, as well as heat capacities at different temperatures. Our thermochemistry data exhibits good agreement with existing values in the literature, verifying the accuracy of our approach. Comparisons against group additivity (GA) method are also presented. The database of thermochemistry quantities developed in this study can be used to improve the training GA or machine learning models. The impact of the developed dataset is illustrated by examining the variation in ignition delay times using the updated thermochemistry values.